A self-generating micro-current dressing and a preparation method thereof

CN122643491BActive Publication Date: 2026-10-09HANGZHOU LANENE BIOTECHNOLOGY CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611115297.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-10-09
Estimated Expiration
2046-07-27

AI Technical Summary

Technical Problem

[0005]本发明的目的在于提供一种自发产生微电流的敷料,通过引入具有多孔结构及纳米片层边缘暴露设计的石墨烯多孔结构作为电极组件,并结合原电池效应自发产生电流,并从石墨烯片层边缘注入体表,以期解决电极-皮肤界面贴合不良及电流分布不均的问题

Benefits of technology

1.良好的皮肤贴合性与电流分布均匀性。本发明采用石墨烯多孔结构作为第二电极的载体,石墨烯纳米片以70°~90°的夹角近垂直排列于无纺布基材表面,并在底面暴露片层边缘部位。该结构具有高柔软性和多孔特性(空隙率≥30%),能够与皮肤表面形成紧密、均匀的接触,显著降低界面接触电阻,避免传统金属电极贴合不良、电流分布不均的问题,提升微电流刺激的舒适性和有效性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122643491B_ABST
    Figure CN122643491B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of self-generated micro-current dressings and preparation method thereof, and the dressing includes non-woven substrate and electrolyte attached therein, the surface of the non-woven substrate is provided with first electrode and multiple second electrodes, and the second electrode includes graphene porous structure and nano metal material loaded in graphene porous structure.The present application uses graphene porous structure as the carrier of second electrode, graphene nanosheet is arranged in the surface of non-woven substrate with the angle of 70°~90° near vertical, and the edge part of sheet layer is exposed in bottom surface.This structure has high softness and porous characteristics (void fraction ≥30%), can form close, uniform contact with skin surface, significantly reduce interface contact resistance, avoid the problem of poor fit, uneven current distribution of traditional metal electrode, improve the comfort and effectiveness of micro-current stimulation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of novel functional textiles, specifically to a fabric that achieves vertical self-discharge by constructing a porous graphene structure and its application in face masks. Background Technology

[0002] Microcurrent stimulation technology has shown great potential in the biomedical field, particularly in wound care and tissue engineering. Studies have shown that microcurrents of appropriate intensity can mimic the endogenous electric field within the body, effectively promoting cell migration, proliferation, and differentiation, accelerating angiogenesis, and exhibiting certain antibacterial activity, thereby significantly improving the healing effect of chronic, difficult-to-heal wounds (such as diabetic foot ulcers and pressure injuries). Furthermore, microcurrents also have applications in skincare. Therefore, developing functional dressings that can safely and conveniently provide continuous microcurrent stimulation has become a hot topic in current medical and aesthetic dressing research.

[0003] Existing technologies have reported various dressing or patch techniques capable of generating microcurrents, such as microcurrent injection using an external power source or in-situ current generation by constructing a galvanic cell. However, several problems remain to be solved. First, traditional metal electrodes (such as metal foils or coatings) are relatively hard, making it difficult to form a tight and uniform fit with soft, irregular, or moist wound surfaces. This poor contact leads to increased interfacial impedance between the electrode and the skin, uneven current distribution, insufficient stimulation in some areas, and potential discomfort or damage in others due to excessively high local current density. Second, metal electrodes are directly exposed to the skin, resulting in limited biocompatibility. Long-term contact may trigger allergic or inflammatory reactions, and the sensations experienced by different users vary significantly. Third, in the field of skincare products, the application time is generally 10-20 minutes. Under low current density, conventional metal electrodes often only have a small amount of metal on the electrode surface participating in the reaction, resulting in low material utilization.

[0004] Therefore, there is an urgent need to develop a new type of dressing that spontaneously generates microcurrents. It should be flexible, have good skin adhesion, high biocompatibility, and be able to generate microcurrents perpendicular to the body surface in a stable and efficient manner. Summary of the Invention

[0005] The purpose of this invention is to provide a dressing that spontaneously generates microcurrents. By introducing a porous graphene structure with exposed edges of nanosheets as an electrode component, and combining this with the galvanic cell effect to spontaneously generate current, which is injected into the skin surface from the edges of the graphene sheets, this invention aims to solve the problems of poor electrode-skin interface adhesion and uneven current distribution. When this fabric is used in a face mask, microcurrent injection can be achieved in specific areas of the face, improving the absorption efficiency of essences, enhancing microcirculation, and improving the skincare effect of the mask.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: a dressing that spontaneously generates microcurrents, comprising a non-woven fabric substrate and an electrolyte attached therein; the surface of the non-woven fabric substrate is provided with a first electrode and a plurality of second electrodes, the second electrodes comprising a graphene porous structure and a nano-metal material loaded in the graphene porous structure; the metal material has a different activity than the metal material forming the first electrode, and when the dressing is applied to a non-insulating object, the first electrode and the second electrode can undergo a spontaneous redox reaction to form a galvanic cell; The graphene porous structure has a contact surface facing the object to which it is applied, with at least a portion of the graphene nanosheets exposed at their edges on the contact surface. When this fabric is applied to the skin surface, a galvanic cell is formed; as a dressing for skin contact, the pH of the electrolyte is generally 4.5-6; the graphene porous structure has good skin adhesion and compatibility.

[0007] The mechanism by which this structure generates in-situ current is as follows: a redox reaction spontaneously occurs in the electrolyte through a potential difference between the electrodes, and the generated charge flows through an external circuit to form a galvanic cell. In this invention, human skin becomes the pathway for the charge to pass through. When the edge of the graphene nanosheet comes into contact with the skin, a microcurrent can be formed in the skin that is substantially perpendicular to the dressing application surface.

[0008] Furthermore, the electrolyte contains functional ingredients. Functional ingredients refer to components that can provide specific therapeutic effects, generally including antibacterial agents (such as silver ions, chitosan, etc.); growth factors (such as cell growth factors); and moisturizing / repairing factors (such as collagen, sodium hyaluronate, ceramides, etc.). When the dressing is in use, the generated 100μA~300μA current induces electroporation in the intercellular spaces of the stratum corneum at a microscale; simultaneously, the microcurrent drives charged nutrients (such as negatively charged hyaluronic acid) to migrate into the deeper layers of the skin (electrophoresis), thereby achieving highly efficient absorption.

[0009] Furthermore, the first electrode is a copper electrode, and the nanomaterial is a single or mixture of zinc, magnesium, and aluminum, with a diameter of 10-50 nm. Classic galvanic cell electrode pairs are selected to effectively generate microcurrents and do not contain heavy metal elements harmful to the skin. The diameter of the nanomaterial is selected from common commercially available products; further reduction in diameter significantly increases cost, while excessively large diameters lead to decreased dispersibility and localized aggregation.

[0010] Furthermore, the copper electrode is strip-shaped, with a width between 0.3 and 3 mm and a thickness between 0.02 and 0.1 mm. The distance between the copper electrode and the second electrode is 5 to 20 mm. Controlling the thickness and width of the copper electrode ensures the formation of the galvanic cell while maintaining the overall breathability, softness, and skin-friendly effect of the fabric, thus reducing overall costs.

[0011] Furthermore, the angle between the graphene nanosheets constituting the porous graphene structure and the plane of the nonwoven fabric substrate is 70°~90°, and the porosity of the porous structure is above 30%. Some graphene sheets have their edges exposed on the bottom surface (the contact surface facing the object being applied), allowing for efficient vertical injection of microcurrents into the skin, significantly enhancing the microcurrent effect. The porous graphene structure with high porosity facilitates contact between the electrolyte and the graphene sheets, thereby promoting the participation of the nano-metal in electrochemical reactions and improving the efficiency of current generation. Simultaneously, the porous graphene nanosheets are highly flexible, causing no stinging or foreign body sensation upon contact with the skin, and can effectively adhere to irregular skin surfaces, reducing contact resistance. This solves the problems of foreign body sensation, uneven current distribution, and allergic discomfort caused by direct contact in traditional metal electrode materials.

[0012] Furthermore, the dressing is a facial mask, and the second electrode is distributed in one or more areas of the T-zone, cheekbones, eye area, and cheeks. The second electrode can be distributed on the mask surface in a non-uniform matrix pattern, for example, with a high-density distribution in one or more areas of the T-zone, cheekbones, and eye area, and a low-density distribution in the cheek areas. The second electrode can also be distributed in a continuous curved pattern (e.g., a spiral), following the direction of facial lymphatic drainage or acupoint matrix distribution, which is more in line with the principles of skin care.

[0013] A method for preparing a dressing that spontaneously generates microcurrents, characterized by comprising the following steps: (1) Substrate pretreatment: The nonwoven fabric is cationically modified to make its surface positively charged; (2) Preparation of graphene gel: Graphene nanosheets are dispersed in water to form a dispersion with a mass concentration of 2-5%. Nanometal materials are added, and ammonia is added to adjust the pH to 8-10. The mixture is stirred evenly to form a mixed dispersion. Then, the mixture is homogenized under high pressure and degassed under vacuum to obtain a graphene gel with a viscosity of 20,000-40,000 cp. (3) Place the cationic nonwoven fabric on a cold plate at -10~-3℃, and apply graphene gel to the nonwoven fabric at fixed points using a dispensing machine. The dispensing needle diameter is 0.5~2mm. After the gel contacts the nonwoven fabric, it stays for 5~15s. Control the dispensing amount and lifting speed to form a cone-shaped graphene gel with a height of 0.2~1mm and a bottom diameter of 0.7~3mm. Freeze and fix it on the cold plate, and then place it in a freeze dryer for freeze drying. When freezing and fixing on the cold plate, ice crystals are formed from bottom to top in the graphene gel by means of ice crystal growth. During the subsequent freeze drying, the ice sublimates and detaches directly, forming a rich pore structure at the ice crystals. The graphene sheets are vertically oriented under the pressure of the ice crystals, so that in the final porous material, some graphene sheets are exposed on the bottom surface with their sheet edges.

[0014] (4) Construct a first electrode in a specific region of the substrate; (5) The electrolyte is loaded onto the fabric to form the dressing.

[0015] In the above steps, charge modification, dispensing, and freeze-drying are key steps. First, by cationic modification of the nonwoven fabric substrate and alkaline treatment of the graphene nanosheet gel, the bonding force between the graphene nanosheets and the nonwoven fabric is greatly improved, avoiding the problem of graphene detachment before use. Second, the graphene gel is fixed to the surface of the nonwoven fabric by vertical dispensing, laying the foundation for the vertical orientation of the graphene nanosheets and avoiding the problem of graphene sheets collapsing and stacking caused by conventional spraying and printing processes. Third, freeze-drying, through the vertically grown ice crystal structure, compresses the graphene nanosheets to align in the vertical direction. During the drying process, the ice crystals sublimate, leaving a rich void structure, thus ultimately forming a porous graphene structure. In the final porous material, some graphene sheets are exposed on the bottom surface with their edge portions.

[0016] Furthermore, the mass ratio of graphene nanosheets to nano-metal materials in step (2) is 1:0.05~0.2. Controlling the ratio of graphene nanosheets to nano-metal materials is to achieve a balance between microcurrent intensity and tactile feel. If the amount of nano-metal added is too low, an effective microcurrent cannot be formed; if the amount added is too high, agglomeration will occur, resulting in an effect similar to that of a pure metal electrode.

[0017] Furthermore, the graphene nanosheets described in step (2) have a size between 50 and 500 nm and a number of layers between 20 and 100. Small-sized graphene nanosheets are chosen to obtain more graphene edges, providing abundant discharge sites at the microscopic level and improving the flexibility of the graphene porous structure. If the graphene nanosheets are too large or have too few layers, the overall flexibility is too high, making them prone to collapsing and adhering to the nonwoven fabric surface. Too many layers reduce dispersibility, hindering molding, and result in too low flexibility and excessively high hardness after vertical orientation.

[0018] Furthermore, to improve the long-term stability of the dressing, a protective layer can be added to the surface of the second electrode to prevent slow internal electrochemical reactions before use, which could prevent the generation of effective microcurrents after skin application. The protective layer can be a PET film, attached to the outer packaging and removed when the packaging is torn open. Alternatively, temperature-sensitive and acid / alkali-sensitive protective materials can be used. For example, during mask application, under body surface temperature (around 35°C) and the action of trace amounts of squalene, triglycerides, and other lipids secreted by the skin, the film rapidly swells, emulsifies, and is absorbed or wiped away, exposing the fresh magnesium-zinc coating surface and immediately activating the galvanic cell reaction.

[0019] The vertical microcurrent testing method is as follows: Two pieces of detached pigskin (approximately 1 mm thick, with the dermis facing down on a non-woven fabric saturated with physiological saline and the stratum corneum facing up) are washed and their surface moisture is wiped off. They are then applied to the first electrode (copper) and the second electrode (graphene / nano zinc) of the dressing, respectively. The probe end of the microcurrent detector is connected to the stratum corneum of the two pieces of pigskin. The dressing is adhered to the surface of the stratum corneum of the pigskin and a constant pressure of 20 g / cm² is applied to ensure that the current generated by the dressing forms a complete circuit through the pigskin. Under the conditions of 32±1°C and 50±10% RH, the short-circuit current is continuously recorded for 120 s at a sampling rate of ≥10 Hz. The average value from the 10th to the 120th s is taken as the steady-state current. At the same time, the background current of the blank dressing (non-woven fabric without metal and graphene) in the same series circuit needs to be subtracted. Each sample is repeated 3 times, and the average value is calculated.

[0020] The beneficial effects of this invention are: 1. Excellent skin adhesion and uniform current distribution. This invention uses a graphene porous structure as the carrier of the second electrode. Graphene nanosheets are arranged nearly vertically on the surface of a non-woven fabric substrate at an angle of 70°~90°, with the edges of the sheets exposed on the bottom surface. This structure has high flexibility and porosity (porosity ≥30%), enabling it to form a tight and uniform contact with the skin surface, significantly reducing interfacial contact resistance, avoiding the problems of poor adhesion and uneven current distribution of traditional metal electrodes, and improving the comfort and effectiveness of microcurrent stimulation.

[0021] 2. Highly efficient and stable vertical microcurrent output. By loading nanomaterials with different activities (such as zinc, magnesium, and aluminum) into a graphene porous structure and forming a galvanic cell system with a first electrode (such as a copper electrode), the dressing can spontaneously generate a microcurrent of 100μA~300μA without an external power source after contact with the skin. The current direction is perpendicular to the skin surface, promoting cell proliferation, migration, and angiogenesis. It is suitable for medical wound healing and skin care penetration enhancement applications. 3. Excellent biocompatibility and safety. The porous structure of graphene exhibits excellent biocompatibility, avoiding allergies, inflammation, or foreign body sensations that may occur when traditional metal electrodes come into direct contact with the skin. Furthermore, the nanomaterials (such as zinc, magnesium, and aluminum) do not contain harmful heavy metals, further ensuring safety during use.

[0022] 4. Significantly enhances the transdermal absorption efficiency of functional ingredients. The electrolyte in the dressing may contain functional ingredients such as growth factors and moisturizing / repairing factors. During use, the microcurrent generated drives charged nutrients (such as hyaluronic acid) to migrate into the deeper layers of the skin through electroporation and electrophoresis, significantly improving the transdermal depth and absorption efficiency of macromolecular active substances, thus enhancing skincare or therapeutic efficacy. Furthermore, the distribution of the second electrode allows for precise application to specific areas, meeting diverse needs.

[0023] 5. Controllable preparation process and high structural stability. The combination of cationic treatment of the substrate and regulation of the graphene gel alkalinity improves the bonding force between the graphene material and the substrate, resulting in good overall structural stability. The preparation process is simple, requires minimal equipment, and allows for mass production. Attached Figure Description

[0024] Figure 1 The image shows a photograph of the dressing prepared in Example 1, wherein a dot-matrix second electrode and a strip-shaped first electrode are disposed on the surface of the nonwoven fabric substrate; 1 is the nonwoven fabric substrate, 2 is the second electrode, and 3 is the first electrode.

[0025] Figure 2 This is a SEM image of the graphene region on the fabric surface in Embodiment 1 of the present invention.

[0026] Figure 3 This is a partial magnification of the SEM image of the graphene region on the fabric surface in Embodiment 1 of the present invention.

[0027] Figure 4 This is a SEM image of the graphene region on the fabric surface in Comparative Example 2 of the present invention. Detailed Implementation

[0028] The present invention will be further described in detail below with reference to specific embodiments.

[0029] Example 1 A dressing that spontaneously generates microcurrents includes a nonwoven fabric substrate and an electrolyte attached therein. The surface of the nonwoven fabric substrate is provided with a first electrode and multiple second electrodes. The second electrodes comprise a graphene porous structure and zinc nanoparticles loaded within the graphene porous structure. The first electrode is a strip-shaped copper electrode. The graphene porous structure has a bottom surface for contact with a substrate, and at least a portion of the graphene sheets exposes its edge portions on the bottom surface, forming contact with the substrate through these edge portions. The specific preparation method is as follows: (1) Substrate pretreatment: Take a 0.2 mm thick spunlace nonwoven fabric, immerse it in a 2% polydiallyldimethylammonium chloride (PDADMAC) solution for 30 minutes, take it out and dry it at 80°C to make the surface of the nonwoven fabric positively charged; (2) Preparation of graphene gel: Graphene nanosheets were dispersed in water to form a dispersion with a mass concentration of 5%. A nano zinc dispersion was added and the pH was adjusted to 8. The mixture was stirred evenly to form a mixed dispersion. Then, the mixture was homogenized under high pressure and degassed under vacuum to obtain a graphene gel with a viscosity of 40,000 cp. The mass ratio of graphene nanosheets to nano zinc was 1:0.1. The size of the graphene nanosheets was 50~100 nm and the number of layers was 20~40. (3) Place the cationic nonwoven fabric on a cold plate at -3℃, apply graphene gel to the nonwoven fabric at fixed points using a dispensing machine with a dispensing needle aperture of 1mm, and hold the gel for 5s after it comes into contact with the nonwoven fabric. Control the amount of gel and the lifting speed to form a cone-shaped graphene gel array with a height of 0.5mm and a bottom diameter of 1.5mm. The array is distributed around the eyes and the cheek area. Then place it in a freeze dryer for freeze drying. (4) Print a copper layer with a width of 2 mm and a thickness of 0.1 mm on the edge of the nonwoven fabric, with a minimum distance of 20 mm from the graphene nanosheet area, and then dry it; (5) The sodium hyaluronate essence aqueous solution with pH 6 is loaded onto the fabric to form the dressing.

[0030] Step (4) A photograph of the fabric after printing the copper layer is shown. Figure 1 As shown, the graphene lattice is distributed around the eyes and cheek area, while the copper layer is distributed along the fabric edges. The microstructure of the graphene lattice is as follows: Figure 2 As shown, the angle between the in-plane orientation of the graphene nanosheets and the plane of the nonwoven fabric substrate is between 70° and 90°. Numerous pores exist between the graphene nanosheets, with an overall porosity of 35.4%. Further observation of the edges of the graphene nanosheets reveals that their stacking thickness is less than 100 nm, and the zinc nanoparticles are distributed on the surface of the graphene sheets without obvious agglomeration. Figure 3 (As shown). After testing, the average vertical current generated within 1 minute under operating conditions was 119μA.

[0031] Example 2 The following method was used to prepare a dressing that spontaneously generates microcurrents: (1) Substrate pretreatment: Take a 0.2mm thick spunlace nonwoven fabric and treat it with plasma for 10 minutes to make the surface of the nonwoven fabric positively charged; (2) Preparation of graphene gel: Graphene nanosheets were dispersed in water to form a dispersion with a mass concentration of 4%. A nano zinc dispersion was added and the pH was adjusted to 10. The mixture was stirred evenly to form a mixed dispersion. Then, the mixture was homogenized under high pressure and degassed under vacuum to obtain a graphene gel with a viscosity of 33000cp. The mass ratio of graphene nanosheets to nano zinc was 1:0.1. The size of the graphene nanosheets was 50~100nm and the number of layers was 70~100. (3) Place the cationic nonwoven fabric on a cold plate at -3℃, apply graphene gel to the nonwoven fabric at fixed points using a dispensing machine with a dispensing needle aperture of 0.5mm, and leave the gel in contact with the nonwoven fabric for 10s. Control the amount of gel and the lifting speed to form a cone-shaped graphene gel array with a height of 1mm and a bottom diameter of 1mm. The array is distributed around the eyes and the cheek area. Then place it in a freeze dryer for freeze drying. (4) Print a copper layer with a width of 1.5 mm and a thickness of 0.1 mm on the edge of the nonwoven fabric, with a minimum distance of 15 mm from the graphene nanosheet area, and then dry it; (5) Load the fabric with an aqueous solution of sodium alginate essence at pH 5 to form the dressing.

[0032] The angle between the in-plane orientation of the graphene nanosheets and the plane of the nonwoven fabric substrate in the obtained mask is between 70° and 90°, and the overall porosity is 41.7%. After testing, the average vertical current generated within 1 minute under use is 144μA.

[0033] Example 3 The following method was used to prepare a dressing that spontaneously generates microcurrents: (1) Substrate pretreatment: Take a 0.25mm thick spunlace nonwoven fabric and treat it with plasma for 10 minutes to make the surface of the nonwoven fabric positively charged; (2) Preparation of graphene gel: Graphene nanosheets were dispersed in water to form a dispersion with a mass concentration of 2%. Aluminum nanosheets were added and the pH was adjusted to 10. The mixture was stirred evenly to form a mixed dispersion. Then, the mixture was homogenized under high pressure and degassed under vacuum to obtain a graphene gel with a viscosity of 20,000 cp. The mass ratio of graphene nanosheets to aluminum nanosheets was 1:0.05. The size of the graphene nanosheets was 470~500 nm and the number of layers was 70~100. (3) Place the cationic nonwoven fabric on a cold plate at -3℃, and apply graphene gel to the nonwoven fabric at fixed points using a dispensing machine with a dispensing needle aperture of 2mm. After the gel contacts the nonwoven fabric, it stays for 15s. Control the amount of dispensing and the lifting speed to form a cone-shaped graphene gel array with a height of 0.3mm and a bottom diameter of 3mm. The array is distributed around the eyes, T-zone and cheek area. Then place it in a freeze dryer for freeze drying. (4) Print a copper layer with a width of 3 mm and a thickness of 0.02 mm on the edge of the nonwoven fabric, with a minimum distance of 12 mm from the graphene nanosheet area, and then dry it; (5) Load the fabric with an aqueous solution of sodium alginate essence at pH 5.5 to form the dressing.

[0034] The angle between the in-plane orientation of the graphene nanosheets and the plane of the nonwoven fabric substrate in the obtained mask is between 70° and 90°, and the overall porosity is 30.1%. After testing, the average vertical current generated within 1 minute under use is 183μA.

[0035] Example 4 The following method was used to prepare a dressing that spontaneously generates microcurrents: (1) Substrate pretreatment: Take a 0.2mm thick spunlace nonwoven fabric and treat it with plasma for 10 minutes to make the surface of the nonwoven fabric positively charged; (2) Preparation of graphene gel: Graphene nanosheets were dispersed in water to form a dispersion with a mass concentration of 4%. Nano magnesium dispersion was added and the pH was adjusted to 8. The mixture was stirred evenly to form a mixed dispersion. Then, the mixture was homogenized under high pressure and degassed under vacuum to obtain a graphene gel with a viscosity of 25000cp. The mass ratio of graphene nanosheets to nano magnesium was 1:0.05. The size of the graphene nanosheets was 180~200nm and the number of layers was 20~40. (3) Place the cationic nonwoven fabric on a cold plate at -10℃, and apply graphene gel to the nonwoven fabric at fixed points using a dispensing machine with a dispensing needle aperture of 2mm. After the gel contacts the nonwoven fabric, it stays for 5s. Control the dispensing amount and lifting speed to form a cone-shaped graphene gel array with a height of 0.2mm and a bottom diameter of 0.7mm. The array is distributed in the T-zone and the apple cheek area. Then place it in a freeze dryer for freeze drying. (4) Print a copper layer with a width of 0.3 mm and a thickness of 0.1 mm on the edge of the nonwoven fabric, with a minimum distance of 5 mm from the graphene nanosheet area, and then dry it; (5) Load the fabric with an aqueous solution of sodium alginate essence at pH 5.5 to form the dressing.

[0036] The angle between the in-plane orientation of the graphene nanosheets and the plane of the nonwoven fabric substrate in the obtained mask is between 70° and 90°, and the overall porosity is 38.6%. After testing, the average vertical current generated within 1 minute under use is 245μA.

[0037] Example 5 The following method was used to prepare a dressing that spontaneously generates microcurrents: (1) Substrate pretreatment: Take a 0.3mm thick spunlace nonwoven fabric and treat it with plasma for 15 minutes to make the surface of the nonwoven fabric positively charged; (2) Preparation of graphene gel: Graphene nanosheets were dispersed in water to form a dispersion with a mass concentration of 4%. Nano magnesium dispersion was added and the pH was adjusted to 8. The mixture was stirred evenly to form a mixed dispersion. Then, the mixture was homogenized under high pressure and degassed under vacuum to obtain a graphene gel with a viscosity of 25000cp. The mass ratio of graphene nanosheets to nano magnesium was 1:0.2. The size of the graphene nanosheets was 180~200nm and the number of layers was 20~40. (3) Place the cationic nonwoven fabric on a cold plate at -10℃, and apply graphene gel to the nonwoven fabric at fixed points using a dispensing machine with a dispensing needle aperture of 1mm. After the gel contacts the nonwoven fabric, it stays for 5s. Control the dispensing amount and lifting speed to form a cone-shaped graphene gel array with a height of 0.7mm and a bottom diameter of 1.5mm. The array is distributed in the T-zone and the apple cheek area. Then place it in a freeze dryer for freeze drying. (4) Print a copper layer with a width of 0.5 mm and a thickness of 0.05 mm on the edge of the nonwoven fabric, with a minimum distance of 10 mm from the graphene nanosheet area, and then dry it; (5) The hyaluronic acid essence aqueous solution with pH 4.5 is loaded onto the fabric to form the dressing.

[0038] The angle between the in-plane orientation of the graphene nanosheets and the plane of the nonwoven fabric substrate in the obtained mask is between 70° and 90°, and the overall porosity is 33.2%. After testing, the average vertical current generated within 1 minute under use is 291μA.

[0039] Comparative Example 1 (1) Take a spunlace nonwoven fabric with a thickness of 0.2 mm and bond it to form zinc pillars with a diameter of 1.5 mm and a height of 0.5 mm. The zinc pillars are distributed around the eyes and the apple cheek area (same as in Example 1).

[0040] (2) Print a copper layer with a width of 2 mm and a thickness of 0.1 mm on the edge of the non-woven fabric, with a minimum distance of 20 mm from the zinc pillar area, and then dry it; (3) Load the fabric with an aqueous solution of sodium hyaluronate essence at pH 6 to form a dressing.

[0041] Tests showed that the dressing generated an average vertical current of 83μA within one minute of use, and there was a noticeable foreign body sensation when wearing it.

[0042] Comparative Example 2 (1) Substrate pretreatment: Take a 0.2 mm thick spunlace nonwoven fabric, immerse it in a 2% polydiallyldimethylammonium chloride (PDADMAC) solution for 30 minutes, take it out and dry it at 80°C to make the surface of the nonwoven fabric positively charged; (2) Spray printing: Graphene nanosheets with a size of 50~100nm and a layer number of 20~40 layers are dispersed in water to obtain a dispersion. The pH value is adjusted to make the surface negatively charged. A template is preset on the surface of non-woven fabric, and the graphene nanosheet dispersion is sprayed onto the template to form a dot matrix pattern on the non-woven fabric. The dot matrix is ​​distributed in the area around the eyes and the apple cheek area, with a dot diameter of 1.5mm and a dot spacing of 0.5mm. There are no graphene dots in other areas. (3) Heating and drying: Place the non-woven fabric with patterned graphene nanosheets in a forced-air drying oven and dry at 80°C for 12 hours; (4) Print a copper layer with a width of 2 mm and a thickness of 0.1 mm on the edge of the nonwoven fabric, with a minimum distance of 20 mm from the graphene nanosheet area, and then dry it.

[0043] A sodium hyaluronate essence solution with a pH of 6 is loaded onto the fabric to form a dressing.

[0044] The microstructure of the obtained mask surface is as follows Figure 4 As shown, graphene nanosheets are laid flat on the surface of the nonwoven fabric and stacked on top of each other, with virtually no gaps. Furthermore, the stacked graphene sheets encapsulate the fibers in the nonwoven fabric, disrupting its original porous structure. Testing revealed that the average vertical current generated within one minute of use was 0~1μA, which is essentially undetectable.

[0045] Comparative Example 3 The following method was used to prepare a dressing that spontaneously generates microcurrents: (1) Substrate pretreatment: Take a 0.2mm thick spunlace nonwoven fabric and treat it with plasma for 10 minutes to make the surface of the nonwoven fabric positively charged; (2) Preparation of graphene gel: Graphene nanosheets are dispersed in water to form a dispersion with a mass concentration of 1%. Nano zinc dispersion is added and the pH is adjusted to 10. The mixture is stirred evenly to form a mixed dispersion. Then, the mixture is homogenized under high pressure and degassed under vacuum to obtain a graphene gel with a viscosity of 14000cp. The mass ratio of graphene nanosheets to nano zinc is 1:0.1. The size of the graphene nanosheets is 50~100nm and the number of layers is 70~100. (3) Place the cationic nonwoven fabric on a cold plate at -3℃, and apply graphene gel to the nonwoven fabric at fixed points using a dispensing machine with a dispensing needle aperture of 0.5mm. After the gel comes into contact with the nonwoven fabric, it is found that due to the low viscosity of the graphene gel, no matter how the dispensing parameters are adjusted, a stable cone-shaped gel cannot be formed. Instead, it spreads on the surface of the nonwoven fabric to form graphene spots with a diameter of 2~3mm. The spots are distributed around the eyes and the cheek area. Then, place it in a freeze dryer for freeze drying. (4) Print a copper layer with a width of 1.5 mm and a thickness of 0.1 mm on the edge of the nonwoven fabric, with a minimum distance of 15 mm from the graphene nanosheet area, and then dry it; (5) Load the fabric with an aqueous solution of sodium alginate essence at pH 5 to form the dressing.

[0046] The resulting mask contains horizontally spread graphene nanosheets with virtually no gaps. Testing showed that the average vertical current generated within one minute of use was only 1-3 μA, which was practically undetectable.

Claims

1. A dressing that spontaneously generates microcurrents, comprising a nonwoven fabric substrate and an electrolyte adhering thereto, characterized in that: The surface of the nonwoven fabric substrate is provided with a first electrode and a plurality of second electrodes. The second electrodes include a graphene porous structure and a nano-metal material loaded in the graphene porous structure. The nano-metal material has a different activity than the metal material forming the first electrode. The graphene porous structure has a contact surface facing the object to which it is applied, and at least a portion of the graphene nanosheets are exposed on the contact surface with their edge ends. The angle between the graphene nanosheets constituting the porous graphene structure and the plane of the nonwoven fabric substrate is 70°~90°.

2. The dressing according to claim 1, characterized in that, The electrolyte contains functional components; functional components are those that can provide specific therapeutic effects.

3. The dressing according to claim 1, characterized in that, The first electrode is a copper electrode, and the nanomaterial is a single substance of zinc, magnesium, and aluminum or a mixture of multiple substances.

4. The dressing according to claim 3, characterized in that, The copper electrode is strip-shaped, with a width between 0.3 and 3 mm and a thickness between 0.02 and 0.1 mm. The distance between the copper electrode and the second electrode is 5 to 20 mm.

5. The dressing according to claim 1, characterized in that, The surface porosity of the graphene porous structure is above 30%, and the nanomaterial is a zinc nanoparticle with a diameter of 10~50nm.

6. The dressing according to claim 1, characterized in that, The dressing is a facial mask, and the second electrode is distributed in one or more areas of the T-zone, cheekbones, eye area, and cheeks.

7. The method for preparing the dressing as described in claim 1, characterized in that, Includes the following steps: (1) Substrate pretreatment: The nonwoven fabric is cationically modified to make its surface positively charged; (2) Preparation of graphene gel: Graphene nanosheets are dispersed in water to form a dispersion with a mass concentration of 2-5%. Nanomaterials are added and ammonia is added to adjust the pH to 8-10. The mixture is stirred evenly to form a mixed dispersion. Then, the dispersion is obtained by high-pressure homogenization and vacuum degassing to obtain a graphene gel with a viscosity of 20,000-40,000 cp. The size of the graphene nanosheets is between 50-500 nm and the number of layers is between 20-100. (3) Place the cationic nonwoven fabric on a cold plate at -10~-3℃, apply graphene gel to the nonwoven fabric at fixed points using a dispensing machine with a dispensing needle diameter of 0.5~2mm, and let the gel remain on the nonwoven fabric for 5~15s after contacting it. Control the amount of dispensing and the lifting speed to form a cone-shaped graphene gel with a height of 0.2~1mm and a bottom diameter of 0.7~3mm. Freeze and fix it on the cold plate, and then place it in a freeze dryer for freeze drying. (4) Construct a first electrode in a specific region of the substrate; (5) Load the electrolyte onto the nonwoven fabric substrate, so that the electrolyte at least wets the first electrode and the second electrode to form the dressing.

8. The preparation method according to claim 7, characterized in that, The mass ratio of graphene nanosheets to nanometal materials in step (2) is 1:0.05~0.2.

Citation Information

Patent Citations

  • Flexible stretchable electronized skin wound repairing paste and preparation method thereof

    CN111297562A

  • Wearable magnesium battery self-powered dressing for chronic wound healing and preparation method and application thereof

    CN120381549A